Pengaruh Green Product Innovation terhadap Nilai Perusahaan melalui Return on Asset - Fathoni, Muhammad Ihtifazhuddin Rizki; Shintyamani, Yogeswari Sista; Dianawati, Wiwiek (Akuntansi & Ekonomika, 2025)
This study explores how environmentally sustainable product innovations contribute to enhancing a company's market valuation, with Return on Assets (ROA) serving as an intervening variable. Adopting a quantitative research design, the analysis draws upon a purposively selected sample of 431 manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2015–2017 period. The dataset was examined through the Partial Least Squares (PLS) approach, facilitated by WarpPLS version 5.0. The findings reveal that innovations aligned with environmental sustainability have a statistically significant and favorable impact on both ROA and firm valuation.